Serum and urinary biomarkers that predict hepatorenal syndrome in patients with advanced cirrhosis. Issue 2 (February 2017) - Yap, Desmond Y.H.; Seto, Wai Kay; Fung, James; Chok, Siu Ho; Chan, See Ching; Chan, Gary C.W.; Yuen, Man Fung; Chan, Tak Mao
Abstract: Background: Prediction of hepatorenal syndrome (HRS) remains difficult in advanced cirrhotic patients. Aims: To evaluate use of serum and urine biomarkers to predict HRS. Methods: We prospectively recruited Child's B or C cirrhotic patients with normal serum creatinine, and followed them for 12 weeks for the development of HRS. Serum Cystatin C (CysC), serum and urine Neutrophil Gelatinase-Associated Lipocalin (NGAL), serum and urine IL-18, serum N -acetyl-β-d glucosaminidase (NAG), urine kidney injury molecule-1 (KIM-1) and urine liver-type fatty acid binding protein (LFABP) were measured at recruitment (baseline), and their relationship with subsequent HRS investigated. Results: 43 patients were included. 12 (27.9%) developed HRS at 7.3 ± 5.1 weeks from baseline. Logistic regression analysis showed that baseline urinary NGAL and urinary KIM-1 were significantly associated with the development of HRS (RR 1.007, 95% CI 1.001–1.012, p = 0.014; RR 1.973, 95% CI 1.002–3.886, p = 0.049). The cut-off values for NGAL and KIM-1 to predict HRS were 18.72 ng/mL and 1.499 ng/mL respectively (AUCs 0.84, p = 0.005; and 0.78, p = 0.008). Conclusion: Urinary NGAL and KIM-1 could serve as biomarkers to predict HRS in advanced cirrhotic patients.